ISUOG Practice Guidelines: intrapartum ultrasound. (4th July 2018) - Ghi, T.; Eggebø, T.; Lees, C.; Kalache, K.; Rozenberg, P.; Youssef, A.; Salomon, L. J.; Tutschek, B.
ABSTRACT: PURPOSE AND SCOPE: The purpose of these Guidelines is to review the published techniques of ultrasound in labor and their practical applications, to summarize the level of evidence regarding the use of ultrasound in labor and to provide guidance to practitioners on when ultrasound in labor is clinically indicated and how the sonographic findings may affect labor management. We do not imply or suggest that ultrasound in labor is a necessary standard of care. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations. Clickhere to see the Video Presentation of this article